(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In the XX century. especially popular are the theory of modernization. Initially using this theory described processes that occurred in western europe in a new and recent time, in the period of transition from agrarian society to industrial. Wherein modernization was a process covering different sides of life society: from economy to culture